CRITICISM ANALYSIS OF THE EFFECTIVENESS OF INDONESIA'S ECONOMIC CRIMINAL POLICY IN THE PERSPECTIVE OF ISLAMIC LAW - Muhammad Irkham Firdaus (Jurnal Cendekia Hukum, 2022)
Economic crime rates tend to be high and generate large losses every year, because one of the biggest factors is the ineffective economic crime policy in providing deterrent and firmness to the perpetrators. Economic crime policies play an important role in creating public welfare, if the economic crime rate is high, it means that the welfare of the community has not been created optimally, so there needs to be efforts to review and fix these criminal policies. This research aims to determine the effectiveness of Indonesia's criminal policy in the perspective of Islamic law, as well as to criticize the economic criminal policy in Indonesia. This research explores data sources from various data on the facts of crimes that occur in Indonesia, which are then analyzed by qualitative methods from the point of view of Islamic law. The results of this research show that economic crime policies have not been effective in tackling economic crimes, because they do not provide a deterrent effect for perpetrators of economic crimes. Whereas in Islam, the prevention of economic crime is divided into two categories, namely jarimah hudud and jarimah ta'zir. Sanctions applied in Islamic law are more of a deterrent effect, because sanctions for serious economic crimes have been determined directly by Allah SWT, then economic criminal policies in Indonesia tend not to achieve their essential goals, namely welfare and social protection for the community, this happens because there are shortcomings in the three stages of implementing economic criminal policies in Indonesia, namely the legislative stage, judicial stage, and executive stage. It is necessary to make a new formulation in the economic criminal policy in Indonesia, namely by specifying the sanctions that will be received by the perpetrators of criminal acts with the sanctions stated in Islamic law, from the point of view of the deterrent effect and the consequences received by the perpetrators.